The Reliability of Ultrasound in the Assessment of Hyaline Cartilage in Rheumatoid Arthritis and Healthy Metacarpal Heads - Cipolletta, Edoardo; Filippucci, Emilio; Di Matteo, Andrea; Tesei, Giulia; Cosatti, Micaela Ana; Di Carlo, Marco; Grassi, Walter (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose i) To assess the inter- and intra-observer reliability of ultrasound (US) in the evaluation of the hyaline cartilage (HC) of the metacarpal head (MH) in patients with rheumatoid arthritis (RA) and in healthy subjects (HS) both qualitatively and quantitatively. ii) To calculate the smallest detectable difference (SDD) of the MH cartilage thickness measurement. iii) To correlate the qualitative scoring system and the quantitative assessment.Materials and Methods US examination was performed on 280 MHs of 20 patients with RA and 15 HS using a very high frequency probe (up to 22 MHz). HC status was evaluated both qualitatively (using a five-grade scoring system) and quantitatively (using the average value of the longitudinal and transverse measures). The HC of MHs from II to V metacarpophalangeal joint of both hands were scanned independently on the same day by two rheumatologists to assess inter-observer reliability. All subjects were re-examined using the same scanning protocol and the same US setting by one sonographer after a week to assess intra-observer reliability.Results The inter-observer agreement and intra-observer agreement were moderate to substantial (k = 0.66 and k = 0.73) for the qualitative scoring system and high (ICC = 0.93 and ICC = 0.94) for the quantitative assessment. The SDD of the MH cartilage thickness measurement was 0.09 mm. A significant correlation between the two scoring systems was found (r = –0.35; p < 0.001).Conclusion The present study describes the main methodological issues of HC assessment. Using a standardized protocol, both the qualitative and the quantitative scoring systems can be reliable.
Keywords: rheumatoid arthritis; hyaline cartilage; metacarpophalangeal joint; ultrasound; musculoskeletal system